K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

22 tháng 8 2022

     1/3 +8/15 : 3/15 

=  1/3 + 8/15 x 15/3

= 1/3 + 8/3

= 9/3

= 3

22 tháng 8 2022

 1/3 +8/15 : 3/15 

=  1/3 + 8/15 x 15/3

= 1/3 + 8/3

= 9/3

= 3

19 tháng 7 2016

a) \(\frac{15}{16}\cdot\frac{4}{3}-\frac{1}{2}:\frac{5}{4}+3\)

\(=\frac{5}{4}-\frac{2}{5}+3\)

\(=\frac{25}{20}-\frac{8}{20}+\frac{60}{20}\)

\(=\frac{77}{20}=3\frac{17}{20}\)

b) \(\left(\frac{2}{3}-\frac{3}{8}\right):\left(\frac{3}{5}+\frac{1}{4}\right)\)

\(=\frac{7}{24}:\frac{17}{20}\)

\(=\frac{35}{102}\)

c) \(\frac{15}{8}\cdot\left(\frac{1}{3}+\frac{1}{8}\right)-\frac{3}{8}:\frac{3}{4}\)

\(=\frac{15}{8}\cdot\frac{11}{24}-\frac{1}{2}\)

\(=\frac{55}{64}-\frac{1}{2}\)

\(=\frac{23}{64}\)

d) \(\frac{20}{21}:\left(\frac{4}{5}-\frac{1}{10}\right)+\frac{13}{15}:\frac{5}{26}\)

\(=\frac{20}{21}:\frac{7}{10}+\frac{52}{15}\)

\(=\frac{200}{147}+\frac{52}{15}\)

\(=4\frac{608}{735}\)

AH
Akai Haruma
Giáo viên
9 tháng 7 2020

Lời giải:

$\frac{-3}{8}.\frac{2}{15}+\frac{-3}{8}.\frac{13}{15}+1\frac{3}{8}$

$=\frac{-3}{8}(\frac{2}{15}+\frac{13}{15})+1+\frac{3}{8}$

$=\frac{-3}{8}.\frac{15}{15}+1+\frac{3}{8}=\frac{-3}{8}+1+\frac{3}{8}=1$

29 tháng 4 2017

\(\dfrac{1}{15}-\dfrac{2}{15}+\dfrac{3}{15}-\dfrac{4}{15}+\dfrac{5}{15}-\dfrac{6}{15}+\dfrac{7}{15}-\dfrac{8}{15}+\dfrac{9}{15}\)

\(=\dfrac{1-2+3-4+5-6+7-8+9}{15}\)

\(=\dfrac{\left(1-2\right)+\left(3-4\right)+\left(5-6\right)+\left(7-8\right)+9}{15}\) => có 4 cặp

\(=\dfrac{\left(-1\right)+\left(-1\right)+\left(-1\right)+\left(-1\right)+9}{15}\)

\(=\dfrac{\left(-1\right).4+9}{15}\)

\(=\dfrac{\left(-4\right)+9}{15}\)

\(=\dfrac{5}{15}=\dfrac{1}{3}\)

5 tháng 5 2018

=7/15 + 3/8 -7/15 +1/8

=> 3/8+1/8

=> 1/2

K MK NHA . CHÚC BẠN HỌC GIỎI

ĐÚNG 100% NHA

5 tháng 5 2018

kết quả bằng 0

28 tháng 2 2019

\(A=\frac{15^8-1+3}{15^8-1}=1+\frac{3}{15^8-1}\)

\(B=\frac{15^8-3+3}{15^8-3}=1+\frac{3}{15^8-3}\)

Ta có: \(15^8-3< 15^8-1\)

=> B>A

16 tháng 3 2018

a )   ( -1/6 + 5/12 ) + 7/12

= -1/6 + ( 5/12 + 7/12 ) 

= -1/6 + 12/12

= -2/12 + 12/12 

=        -10/12

=        -5/6

a: =1/8-1/8+2/5=2/5

b: =(-1/15-14/15)+(23/27+31/27)=2-1=1

c: \(=\dfrac{3}{7}\left(\dfrac{22}{21}+\dfrac{5}{21}+\dfrac{15}{21}\right)=\dfrac{3}{7}\cdot2=\dfrac{6}{7}\)

d: \(=\dfrac{-8}{9}\cdot\dfrac{3}{2}+\dfrac{1}{9}\cdot\dfrac{-3}{2}=-\dfrac{3}{2}\)